Mufassir dan Kitab Tafsir Nusantara (TafsirTurjumun al-Mustafid Karya Abd. Rauf As-Singkilli) - Abid Syahni (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2019)
Abd al-Ra`uf al-Sinkilli, also known as teungku Syakh Kualam, is a quite productive Indonesian ulama, he took his education from his own birthplace, Singkil area, to the Arabian Land. Among his works is the book Tarjūman al-Mustafīd, an interpretive book which is recognized as the first interpretation book produced in Indonesia using the Malay language. This book has been published many times in various regions of the world. The method of writing Tarjuman al-Mustafid’s interpretation, we can see from two angles namely the angle of interpretation and the angle of meaning. When we explore from the point of view of the interpretation that explains the order of the verse and the explanation of the aspects and contents of the content of the verse, this is the tahlili method. Meanwhile, when viewed from the perspective of the meaning explained from the Tafsir, the method applied in writing the Tafsir is the ijmali method. Because the explanation is concise, concise, easy to understand and suitable for beginners. From this explanation makes the interpretation of Tarjūman al-Mustafīd very special, not only composed by the great ʻulama but also as the first interpretation in Malay which is complete 30 juz.